Знахарь. Путевка в "Кресты": роман / Б. К. Седов - Седов Б. К. (Воровской закон, 2002)
Экземпляры: ф.22 (2003) / Инвентарный номер: 46630 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 28 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44